High prevalence of radiographic erosions in early, untreated PsA: results from the SpARRO cohort - Richard J Wakefield; Paul Emery; Helena Marzo-Ortega; Dennis G McGonagle; Ai Lyn Tan; Andrea Di Matteo; Philip Helliwell; Gabriele De Marco; Or Hen; Sayam R Dubash (RMD Open, 2024)
Aims To investigate the prevalence and distribution of bone erosions in an early psoriatic arthritis (PsA) population using conventional radiography (CR) and to explore the agreement between CR and ultrasound (US) detected bone erosions.Methods Newly diagnosed, treatment naïve PsA patients fulfilling the ClASsification for Psoriatic Arthritis (CASPAR) classification criteria of ≤5 years symptom duration were recruited as part of the Leeds Spondyloarthropathy Register for Research and Observation and underwent CR and US examination of hands and feet.Results Overall, 4655 hand and feet joints were assessed in 122 patients. CR erosions were detected in 24.6% (n=30) with lowest prevalence seen below 8 months of symptoms (17.5% vs 24.3%>24 months). The number of erosions was higher on CR (1.55% (63/4,655); US 1.04% (34/3,270)), with 5th metatarsophalangeal (MTP) joint being the most affected site in both CR (5.21% (11/211)) and US (7.14% (15/210)). Erosions in CR were more evenly distributed compared with US where three-quarters of the total number of bone erosions were detected in wrists, second metacarpophalangeal (MCP) and fifth MTP joints. Most joints had almost perfect prevalence-adjusted bias-adjusted kappa values ranging from 0.91 to 1.Conclusions Erosions were seen in a quarter of patients with newly diagnosed, untreated PsA with a declining trend around the 8-month symptom duration cut-off. High levels of agreement between CR and US were seen with CR detecting more erosions. A focused US assessment of the wrist, second MCP and fifth MTP joints may be useful to detect bone erosions in early PsA.